A preliminary study on the neurocognitive deficits associated with loneliness in young adults - Jin, Eunju; Hwang, Samuel Suk-Hyun (Frontiers in Public Health, 2024)
Experience of loneliness is universal and may have adverse effect on neuro-cognitive functioning even at younger age. Using a comprehensive neuro-cognitive function test battery, we examined the possible negative effects of loneliness on neuro-cognitive functioning in young adults. High-lonely group and low-lonely group were screened using the UCLA Loneliness Scale v.3 and measures pertaining to the domains of intelligence, attention, memory, executive function, and psychomotor functioning were tested and compared. As depression and anxiety were significantly higher in the high-lonely group, analysis of covariance was conducted. As the result, high-lonely group showed significantly poor performance on measures of executive function and attention prior to controlling for depression and anxiety, and executive function retained its significance even after controlling for these variables. Additional analysis showed that depression and anxiety did not significantly mediate the relationship between loneliness and neuro-cognitive functioning. Such results suggest that loneliness is likely to negatively affect executive functioning and attention in early adulthood then progressively spread to other domains of cognitive functioning as reported in elderly population. Limitations and implications of the present study were considered were addressed.